Synthesis of a derivative of α-D-Glcp(1->2)-D-Galf suitable for further glycosylation and of α-D-Glcp(1->2)-D-Gal, a disaccharide fragment obtained from varianose - Marino, Carla; Lima, Carlos; Mariño, Karina; de Lederkremer, Rosa M. (Beilstein Journal of Organic Chemistry, 2012)
The presence of galactofuranoyl units in infectious microorganisms has prompted the study of the metabolic pathways involved in their incorporation in glycans. Although much progress has been made with respect to the biosynthesis of β-D-Galf-containing glycoconjugates, the mechanisms by which α-D-Galf units are incorporated remain unclear. Penicillium varians is a non-pathogenic fungus that produces varianose, a polysaccharide containing both α- and β-D-Galf units, which can be used as a model for biosynthetic studies on α-D-Galf incorporation. Synthetic oligosaccharide fragments related to varianose are useful as potential substrates or standards for characterization of the α-galactofuranosyl transferases. In this paper we report a straightforward procedure for the synthesis of α-D-Glcp(1→2)-D-Gal (1) and the use of this compound to monitor the natural disaccharide released from varianose by mild acid degradation. The synthesis, performed by the glycosylaldonolactone approach, involved a glucosylgalactofuranose derivative, suitable for the synthesis of higher oligosaccharides with an internal D-Galf.
Keywords: α-D-galactofuranose; glucosylgalactofuranose; glycosylaldonolactone; Penicillium varians; varianose